AFFIXATION OF TENGGER JAVANESE LANGUAGE: AN ETHNOMORPHOLOGICAL APPROACH - Arliansyah, Adinda Amirah; Andayani, Sri; Tjahyadi, Indra (Program Studi Bahasa Inggris, Universitas Panca Marga, 2023)
Tengger is one of the tribes on the island of Java, especially East Java. As the general public knows, the Tengger tribe has its daily language, namely Tengger language. Even though this tribe is located in the middle of an area that experiences language mixing, the Tengger tribe still uses their language in everyday life. The language, which more or less still uses Old Javanese, is an interesting object to research, one of which is the word affixes used in the Tengger language. This research uses a qualitative descriptive approach to analyze the problem. The research was carried out using the interview method so that researchers could understand what affixations are used in the Tengger language. After obtaining data results from sources, this research validated the data with people who were experts in the Tengger language. The results of data analysis from affixations in the Tengger language can be concluded that ten types of prefixes were found in the Tengger language, namely di-, N-, kə-, neʔ-, mə-, digə-, ka-, pi-, paN-, taʔ-. Two infixes from the data analysis results are -əl-, and -əm-. Seven suffixes are found in the Tengger language: -an, -nan, -e, -ne, -a, -ən, -ana. So, the total is 19 kinds of affixes found in the Tengger language.